Cytomegalovirus retinitis as an adverse immunological effect of pulses of vincristine and dexamethasone in maintenance therapy for childhood acute lymphoblastic leukemia1. Issue 2 (13th September 2012) - Moritake, Hiroshi; Kamimura, Sachiyo; Kojima, Hitomi; Shimonodan, Hidemi; Harada, Masako; Sugimoto, Takako; Nao‐i, Nobuhisa; Nunoi, Hiroyuki
Abstract We describe a 5‐year‐old female with acute lymphoblastic leukemia (ALL) who suffered from cytomegalovirus (CMV) retinitis during maintenance therapy consisting of 6‐mercaptopurine (6‐MP) and methotrexate (MTX) with pulses of vincristine (VCR) and dexamethasone (DEX). Administration of anticytomegaloviral drugs led to a complete regression of active retinitis. Her low CD4 positive T cells and serum immunoglobulin G (IgG) recovered when maintenance therapy was resumed without VCR and DEX. The patient has been in complete remission (CR) for more than 5 months after completion of maintenance therapy without recurrence of CMV retinitis. Pediatr Blood Cancer 2013;60:329–331. © 2012 Wiley Periodicals, Inc.